Surgical Strategies in the Management of Raynaud's Phenomenon: Comparative Analysis of Trends and Effectiveness Incorporating New Clinical Data - Cygnarowicz, Aleksandra; Turemka, Mariola; Hosseinnejad, Negar; Sacher, Karolina; Wojtas, Aneta Klaudia; Zabojska, Krystyna; Biskupski, Mikołaj; Korotko, Urszula; Witowska, Kinga; Mandziuk, Aneta (Journal of Education, Health and Sport, 2024)
Introduction and objective Raynaud's phenomenon is a condition of unknown origin and complex pathophysiology, characterized by an excessive sensitivity to vasoconstriction of arteries in the hands, feet, auricles and nose, leading to a characteristic constellation of symptoms with at least two phase course: pallor and cyanosis. The aim of this work is to review surgical techniques for treating patients with Raynaud's phenomenon and to attempt to determine whether the results of current studies may support earlier initiation of surgical treatment. Review methods To prepare this review, the authors used PubMed and Google Scholar databases, searching the following keywords: "Raynaud's phenomenon", "Raynaud's phenomenon surgical management", "digital artery reconstruction" "sympathectomy", "arterial bypass", "venous arterialization". The search results were limited to studies in English from 2006 to 2024, as well as key studies from earlier years. Brief description of the state of knowledge Currently, patients who are qualified for surgical treatment in the course of Raynaud's phenomenon are those who have symptoms or non-healing ulceration despite of an appropriate pharmacological treatment. Current therapy using calcium channel blockers does not bring full satisfaction to patients. Therefore, the search for optimal therapy continues, with a particular focus on the development of microsurgical treatment techniques. Summary The occurrence of Raynaud's phenomenon, especially the pain and discomfort associated with it, significantly reduces patients' quality of life. Due to advances in the field of microsurgery and the discovery of new mechanisms responsible for the development of Raynaud's phenomenon, earlier patient qualification for surgical procedures is becoming possible. This gives hope for further development of surgical approaches and improvements in treatment outcomes. Keywords: Raynaud's phenomenon; sympathectomy; arterial bypass; venous arterialization